Doping Effects and Charge‐Transfer Dynamics at Hybrid Perovskite/Graphene Interfaces. Issue 20 (6th August 2018) - Brus, Viktor V.; Lang, Felix; Fengler, Steffen; Dittrich, Thomas; Rappich, Jörg; Nickel, Norbert H.
Abstract: In this work doping effects and charge transfer processes at the perovskite/graphene interface in the dark and under illumination are investigated. Hall effect, field effect, and surface photovoltage measurements suggest that hybrid perovskite layers induce strong n‐type doping of graphene after annealing at low temperature (330 K) in vacuum. It is found that the observed photoinduced changes in the electronic properties of graphene, functionalized by a hybrid organic–inorganic perovskite layer, are caused by two independent mechanisms with different time scales: (i) a fast collection of photogenerated holes by graphene from the perovskite layer and (ii) a slow ion rearrangement in the perovskite lattice at the perovskite/graphene interface. The observed annealing‐induced n‐type and photoinduced p‐type doping effects allow to reversibly switch the type of conduction of the perovskite/graphene system. Abstract : Hybrid perovskite layers induce strong n‐type doping of graphene after annealing at low temperature in vacuum. The photo‐induced changes in the electronic properties of the perovskite/graphene system are caused by two independent mechanisms with different time scales. The n‐type and photo‐induced p‐type doping effects allow to reversibly switch the type of conduction of the perovskite/graphene system.